2010
DOI: 10.1007/s00737-010-0148-4
|View full text |Cite
|
Sign up to set email alerts
|

“My children and my home”: the most recent and challenging stressors of HIV-positive women

Abstract: Because of negative health consequences and differences in exposure and vulnerability to stressful encounters, it is important to examine and understand the stressful experiences faced by women living with HIV. The goal of this study was to examine the most recent and challenging stressors faced and coping strategies adopted by a sample of women living with HIV. Using mixed methodology, narratives of six women's most recent and stressful experience and answers to the Ways of Coping questionnaire were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…The diversity of and vulnerability to stressful events that HIV-positive women are likely to encounter are inherently different than that faced by HIVpositive men or HIV negative women (Shannon et al 2008). Ndlovu et al describes that child-related stressors are the most challenging stressors faced by HIV-positive women and seeking social support was an important component of coping response for the participants in that study (Ndlovu et al 2010). Greene et al highlight the complex and unique needs of HIV-positive parents who live with and care for their children and the central role that housing plays in their lives.…”
mentioning
confidence: 87%
“…The diversity of and vulnerability to stressful events that HIV-positive women are likely to encounter are inherently different than that faced by HIVpositive men or HIV negative women (Shannon et al 2008). Ndlovu et al describes that child-related stressors are the most challenging stressors faced by HIV-positive women and seeking social support was an important component of coping response for the participants in that study (Ndlovu et al 2010). Greene et al highlight the complex and unique needs of HIV-positive parents who live with and care for their children and the central role that housing plays in their lives.…”
mentioning
confidence: 87%
“…A number of research studies have examined the housing precarity of Aboriginal people, African Diasporic (Black racial identity) communities, women, families and older people with HIV (Furlotte et al 2012;Greene et al 2010;Monette et al 2009Monette et al , 2011Ndlovu, Ion, and Carvalhal 2010;Riley et al 2007;Tucker et al 2009). This evidence compliments the demographic diversification of the epidemic in Canada, where key populations at risk for HIV include men who have sex with men (MSM), 2 people who use drugs, women, Aboriginal people and people from countries where HIV is endemic.…”
Section: Precarious Housing In Canadamentioning
confidence: 99%
“…However, to our knowledge, only three studies have qualitatively investigated the psychosocial stressors of HIV-infected women (Hackl, Somlai, Kelly, & Kalichman, 1997; Ndlovu, Ion, & Carvalhal, 2010; Semple, Patterson, Temoshok, & McCutchan, 1993). Two studies assessed the stressors of HIV-infected women and found that HIV-related health concerns and issues central to HIV (e.g., experiences of HIV-related stigma) were the most salient stressors (Hackl et al, 1997; Semple et al, 1993).…”
mentioning
confidence: 99%
“…However, these studies were done before the widespread availability of HAART. A more recent qualitative study found that inadequate housing and serving as the primary caregiver for children were the most prominent stressors (Ndlovu et al, 2010). However, this study sampled only six HIV-infected women.…”
mentioning
confidence: 99%
See 1 more Smart Citation